Associations of multiple carotenoid co-exposure with all-cause and cause-specific mortality in US adults: a prospective cohort study - He, Qinglin; Yuan, Chunling; Liu, Zhihui; Wei, Xiaoxia (Frontiers in Nutrition, 2024)
Background: Epidemiological evidence regarding circulating carotenoids and mortality risk remains conflicting, and most studies focus on individual carotenoid impacts. This study aimed to elucidate the effects of co-exposure to multiple serum carotenoids on mortality risk. Methods: We enrolled 22,472 participants aged ≥20 from National Health and Nutrition Examination Survey (NHANES) III (1988–1994) and NHANES 2003–2006. Baseline serum levels of 5 major carotenoids (α-carotene, β-carotene, lycopene, β-cryptoxanthin, and lutein/zeaxanthin) were assessed, and individuals were followed up until December 31, 2019. Carotenoid co-exposure patterns were identified using the K-means method. Cox proportional hazard models were used to investigate the associations between carotenoid exposure and mortality risk. Results: During a median follow-up of 16.7 years, 7,901 deaths occurred. K-means clustered participants into low-level, low-lycopene, high-lycopene, and high-level exposure groups. In the fully adjusted model, low-lycopene, high-lycopene, and high-level exposure groups had significantly lower all-cause mortality risks compared to the low-level group, with hazard ratios (HRs) and 95% confidence intervals (CIs) of 0.79 (0.72, 0.87), 0.75 (0.67, 0.84), and 0.67 (0.61, 0.74), respectively. For cardiovascular disease mortality, the high-lycopene exposure group had a 27% reduced risk (HR: 0.73, 95% CI: 0.61-0.86), and the high-level exposure group had a 21% reduced risk (HR: 0.79, 95% CI: 0.67-0.93). For cancer mortality, the high-lycopene and high-level exposure groups had 30% and 35% lower risks, with HRs (95% CIs) of 0.70 (0.57, 0.86) and 0.65 (0.54, 0.79), respectively. Conclusion: This study revealed that co-exposure to multiple serum carotenoids was associated with reduced mortality risk, highlighting the potential health benefits of increased carotenoid intake. Further investigation is warranted to elucidate the underlying mechanisms of interactions among different carotenoids.